1977
DOI: 10.1111/j.1600-0404.1977.tb05632.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Ischemic Stroke in Young Adults

Abstract: The report provides prognostic information on 60 patients (aged 16 to 40 years) with ischemic stroke. Immediate mortality from stroke is low and long-term mortality is due to other causes than cerebrovascular disease. The recovery from neurological deficits is good except for patients with occlusions of the internal carotic artery or the proximal parts of the middle cerebral artery. Reinfarction is rare (about 0.5 per cent annually) and other late neurological complications do not seriously affect long-term pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 5 publications
1
24
2
1
Order By: Relevance
“…Stroke associated with migraine, stroke due to extracranial artery dissection, and patients with an unknown etiology have been associated with lower risk of recurrence [2,12,13,20,32,33].…”
Section: Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Stroke associated with migraine, stroke due to extracranial artery dissection, and patients with an unknown etiology have been associated with lower risk of recurrence [2,12,13,20,32,33].…”
Section: Recurrencementioning
confidence: 99%
“…The most important methodological limitations in most of these studies are the retrospective design, but it is not so important to evaluate the long-term consequences of stroke, since events as recurrence, death, and disability can be easyly and accurately evaluated with this methodology. The review of the clinical records (including periodic outpatient reviews) complemented with telephone interviews is the main tools for obtaining information about the patients' functional status after the stroke in the main studies about consequences of stroke in the young [9][10][11][12][13][14], including prospective series [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies reported marital problems after stroke, including separation or divorce. 3,46,52,[62][63][64][65]76,85 Six of these reported that marital problems were a direct consequence of the stroke. 46,52,62,65,76,85 One study reported that 5% of the sample had experienced deterioration in the spousal relationship, 65 whereas another found that 38% of couples had experienced conflict since the stroke.…”
Section: Family Relationshipsmentioning
confidence: 99%
“…6 Hypertension was defined as treatment with antihypertensive drugs before stroke onset or the introduction of antihypertensive treatment before discharge. Diabetes mellitus was considered present if it was diagnosed before stroke onset (patient on glucose-lowering diet or medication) or during the hospital stay (fasting plasma glucose Ͼ7.7 mmol/L).…”
Section: Patientsmentioning
confidence: 99%